1996
DOI: 10.1007/bf00184602
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-epithelial interactions in the bladder

Abstract: During bladder development, undifferentiated mesenchymal and epithelial cells undergo an orderly sequence of differentiation defined by the expression of smooth-muscle (alpha-actin, myosin, vinculin, desmin, vimentin, and laminin) and epithelial (cytokeratins 5, 7, 8, 14, 18 and 19) protein markers. This process requires mesenchymal-epithelial interactions with bladder epithelium (urothelium) necessary for the differentiation of bladder smooth muscle. Peptide growth factors such as keratinocyte growth factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
1
39
1
Order By: Relevance
“…Appropriate epithelial-mesenchymal interaction is essential for normal bladder development; in the absence of bladder epithelium, bladder smooth muscle does not develop normally (Baskin et al, 1996a). To examine how the p63-null epithelium affects the adjacent mesenchyme, we studied the expression of Msx1, a homeobox gene that is induced in the mesenchyme by an epithelium-derived signal.…”
Section: Failure Of Ventral Ugs Mesenchymal Induction and Proliferatimentioning
confidence: 99%
“…Appropriate epithelial-mesenchymal interaction is essential for normal bladder development; in the absence of bladder epithelium, bladder smooth muscle does not develop normally (Baskin et al, 1996a). To examine how the p63-null epithelium affects the adjacent mesenchyme, we studied the expression of Msx1, a homeobox gene that is induced in the mesenchyme by an epithelium-derived signal.…”
Section: Failure Of Ventral Ugs Mesenchymal Induction and Proliferatimentioning
confidence: 99%
“…These paracrine-signaling events orchestrate the development and functions of organs establishing morphology during organogenesis and maintaining adult differentiation. Previous studies have demonstrated that cellcell signaling between the stroma and epithelium are integral for correct bladder development (Baskin et al, 1996a(Baskin et al, ,b, 2001DiSandro et al, 1998;Liu et al, 2000;Staack et al, 2005). Studies by Baskin and co-workers have demonstrated reciprocal cellcell signaling between the stromal and epithelial compartments.…”
Section: Introductionmentioning
confidence: 98%
“…The long-term results of penile-straightening Mesenchymal-epithelial interactions are necessary for normal bladder, uterine and prostatic development procedures performed in young children are not known. In adults, the incidence of impotence after correcting [21][22][23]. In the urogenital tract, mesenchyme induces and specifies patterns of epithelial morphogenesis, penile curvature is extremely low, despite the many different surgical techniques [1].…”
Section: Resultsmentioning
confidence: 99%
“…The present results show the highest density of smooth muscle was adjacent to the urethral epithelium just below the cavernosal bodies that the concept of a small strip of dorsal neurovascular bundle supplying the glans is incorrect, in that the (Figs 2b,e, 3d,4b,d). It may be that, as in the bladder, prostate and uterus, the urethral epithelium is necessary nerves completely surround the cavernosal bodies, piercing the glans not just at the 11 and 1 o'clock positions, to induce smooth muscle development in the penis [21,23]. but along the entire side of the tunica (Figs 1-4,6,7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation